The role of the Donetsk oblast construction sector in renovation of the territories - Tochonov, I.; Kalashnikova, T.; Hordiienko, V. (Економічний вісник Донбасу, 2017)
The state of the construction industry in Donetsk Oblast is assessed, in particular, the damage to infrastructure facilities that were destroyed as a result of armed conflict in Donbas are analyzed. The amounts of completed construction work by types of construction products in the cities and districts (raions) of Donetsk Oblast are analyzed. Proposals on the development of the construction industry in Donetsk Oblast in the issues of solving the housing problems of the population are given. Оцінено стан будівельної галузі Донецької області, зокрема проаналізовано пошкоджені об’єкти інфраструктури, які були зруйновані внаслідок воєнних дій на Донбасі. Проаналізовано обсяги виконаних будівельних робіт за видами будівельної продукції по містах та районах Донецької області. Надано пропозиції щодо розвитку будівельної галузі Донецької області в питаннях вирішення житлових проблем населення. Оценено состояние строительной отрасли Донецкой области, в частности проанализированы поврежденные объекты инфраструктуры, которые были разрушены в результате военных действий на Донбассе. Проанализированы объемы выполненных строительных работ по видам строительной продукции по городам и районам Донецкой области. Даны предложения по развитию строительной отрасли Донецкой области в вопросах решения жилищных проблем населения.